Amateur and professional ice hockey player hydration status and urine specific gravity values before and after training in winter conditions - Ozolina, L.; Pontaga, I.; Kisis, I. (LASE Journal of Sport Science, 2014)
The aim of our investigation was to determine and compare the pre- and post-training body hydration status in professional and amateur male ice hockey players consumed the drinks according to their thirst sensation in winter conditions. Materials and methods: 11 amateur and 23 professional ice hockey players participated in the investigation. The players were weighted before and after training using precise scales. The body mass composition of every athlete was determined by the body composition analyzer. Every player collected mid-stream urine specimens before and after the training. Urine specific gravity (USG) was measured by urine refractometer. Results: 56% of the professional ice hockey players and 82% of amateur players were hypohydrated before training according to their USG values ? 1.020, 5% of professional players were dehydrated their USG values ? 1.030. After the training with duration of 1.5 hours the mean body mass decreased for 0.9±0.5% of pre-training value in amateur players and for 1.6±0.8% in professionals (p=0.005). After the training the professional players` hydration status worsened: 66% were hypohydrated and 26% dehydrated according to USG, the mean USG after training was significantly higher than before it (p=0.011). USG after training did not change in amateur players: their mean USG values before and after training did not differed significantly (p=0.677). Conclusions: Fluid uptake according to thirst sensation in winter conditions cannot compensate the fluid loss at rest and during training especially in professional ice hockey players. The body mass loss exceeded value critical for performance-2 % in one third part of professionals. The differences between two groups can be explained by higher intensity of exercises during training, the better physical conditioning and greater sweating rate in professional players in 56 comparison with amateurs, which causes close to twice greater uncompensated fluid loss in professionals than in amateurs.